Effect of specimen size in determining ductile to brittle transition temperature. (14th November 2015) - Moitra, A.; Krishnan, S. A.; Sasikala, G.; Bhaduri, A. K.; Jayakumar, T.
Abstract : Ductile to brittle transition temperature (DBTT) for 9Cr–1Mo steel has been determined from Charpy impact testing for full size and subsized specimens. DBTT was obtained at various percentage of upper shelf energy (USE). Assuming that most of the energy is spent in crack initiation, notch root volumes of subsized specimens ( V NS ) were normalised with full size specimen ( V NF ), and a power law relationship between DBTT and notch root volume has been established. From finite element method, it is observed that the sum of von Mises stress (σeq ) and hydrostatic stress (σh ) reaches ∼2400 MPa (fracture stress, σf *) as the specimen dimension decreases at a temperature corresponding to 33% USE. This corresponds to ∼68 J of full size specimen used in the determination of nil ductility transition temperature.